Group Guidance Using the Halaqah Method to Improve Student Interpersonal Communication - Nurul Fadilah (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The aim of this research was to obtain a group guidance service using the halaqah method which is effective for improving students' interpersonal communication. This study uses experiments with a quantitative approach. The population of this study was class X students at SMK Negeri 2 Tarakan in the 2022/2023 academic year, which consisted of 129 students. The subjects of this research were 18 students who were Muslim in Tarakan State Vocational School 2 Class X TAV 2. Methods of data collection using a scale and observation. The data analysis used is descriptive statistical analysis and inferential statistical analysis. Based on the results of the research, the pre-test and post-test were carried out on students of class X TAV 2 at SMK Negeri 2 Tarakan. The results showed that group counseling using the halaqah method was effective in improving students' interpersonal communication. The implications of the group guidance halaqah method can be used as a reference to improve student interpersonal communication. Halaqah method group guidance will be effective if it is carried out in a more systematic and planned manner and with more meetings.